Toxicological Assessment of Particulate and Metal Hazards Associated with Vaping Frequency and Device Age - Jennifer Jeon; Qian Zhang; Patrick S. Chepaitis; Roby Greenwald; Marilyn Black; Christa Wright (Toxics, 2023)
Electronic nicotine delivery systems (ENDS) aerosols are complex mixtures of chemicals, metals, and particles that may present inhalation hazards and adverse respiratory health risks. Despite being considered a safer alternative to tobacco cigarettes, metal exposure levels and respiratory effects associated with device aging and vaping frequency have not been fully characterized. In this study, we utilize an automated multi-channel ENDS aerosol generation system (EAGS) to generate aerosols from JUUL pod-type ENDS using tobacco-flavored e-liquid. Aerosol puff fractions (1–50) and (101–150) are monitored and sampled using various collection media. Extracted aerosols are prepared for metal and toxicological analysis using human primary small airway epithelial cells (SAEC). ENDS aerosol-mediated cellular responses, including reactive oxygen species (ROS), oxidative stress, cell viability, and DNA damage, are evaluated after 24 h and 7-day exposures. Our results show higher particle concentrations in later puff fractions (0.135 mg/m3) than in initial puff fractions (0.00212 mg/m3). Later puff fraction aerosols contain higher toxic metal concentrations, including chromium, copper, and lead, which elicit increased levels of ROS followed by significant declines in total glutathione and cell viability. Notably, a 30% increase in DNA damage was observed after 7 days because of later puff fraction exposures. This work is consistent with ENDS aerosols becoming more hazardous across the use of pre-filled pod devices, which may threaten respiratory health.